Evaluation on quality of life improvement in patients after microvascular decompression treatment of hemifacial spasm - Lan, Le Thi Ngoc; Ha, Duong Dai; Hoang Anh, Pham (Tạp chí Nghiên cứu Y học, 2025)
Hemifacial spasm (HFS) while not a life-threatening condition, still causes significant facial disfigurement and consequently decreases patient’s quality of life (QoL). A retrospective study was conducted at the Neurosurgery Department of Viet Duc University Hospital with 36 patients with HFS who underwent MVD. The clinical data of these patients were collected prospectively and consecutively from June 2023 to June 2024. The validated, questionnaire (EQ-5D-5L, EQ-VAS, PHQ-9, Jankovic Rating Scale) was used to evaluate the QoL in patients with HFS after MVD. Among 36 participants enrolled in this study, there were 6 males and 30 females with a mean age of 49.02 ± 10.03 years old. The mean score of preoperative JRS and postoperative JRS were 3.17 ± 0.38 and 1.44 ± 1.38 respectively. There was a correlation of severity of HFS with patient’s QoL in physical and mental domains (p < 0.05). There were significant improvements of social life frequency between pre- and postoperative. HFS affects QoL both physically and mentally. Patients with severe HFS symptoms or comorbidities are at higher risk of worse QoL. MVD not only provides high spasm-relief rate, but also leads to significant higher QoL after surgery.